La Antígona de Lacan : comentario al apartado "la esencia de la tragedia" del seminario 7, la ética del psicoanálisis (2010)
ABSTRACT: The purpose of the present paper is to show the most important elements in Lacan´s presentation related to the section titled The Essence of Tragedy in his seminar The Ethics of Psychoanalysis, by extracting from it the nodal aspects between ethics and tragedy. This commentary, despite being ruled by the lessons in the above mentioned section, will use Sophocles’ works as a direct reference to find the aspects dealing with tragedy. This is an attempt to set some consequences related to the analytical experience and the statute of the subject and the Other within the frame of the ethics of tragedy.